1979
DOI: 10.1109/tbme.1979.326392
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Existence of Electrically Located Acupuncture Points

Abstract: in Partial Fulfillment of the Requirements for the Degree of MASTER OF ENGINEERING Approved May, 1976 Moll ACKNOWLEDGMENTS I would like to thank those people who volunteered their time to serve as subjects for my study. In addition, I am Indebted to Professors Blair A. Rowley and Dwane E. Anderson for their advice in preparing this paper. I would also like to thank the other menders of my committee. Professors William B. Jarzembski and Mohamed M. Ayoub, for their assistance. Finally, I would like to thank my f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Sixteen articles representing 18 studies were maintained in the review and evaluated in detail. Nine studies evaluated the acupuncture point [Reichmanis et al, 1975[Reichmanis et al, , 1976Hyvarinen and Karlsson, 1977;McCarroll and Rowley, 1979;Poon et al, 1980;Falk et al, 2000;Pearson et al, 2007], while the other nine evaluated the acupuncture meridian [Reichmanis et al, 1977a[Reichmanis et al, ,b, 1979Hu et al, 1992;Zhang et al, 1999;Martinsen et al, 2001;Johng et al, 2002;Lee et al, 2003;Ahn et al, 2005].…”
Section: Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen articles representing 18 studies were maintained in the review and evaluated in detail. Nine studies evaluated the acupuncture point [Reichmanis et al, 1975[Reichmanis et al, , 1976Hyvarinen and Karlsson, 1977;McCarroll and Rowley, 1979;Poon et al, 1980;Falk et al, 2000;Pearson et al, 2007], while the other nine evaluated the acupuncture meridian [Reichmanis et al, 1977a[Reichmanis et al, ,b, 1979Hu et al, 1992;Zhang et al, 1999;Martinsen et al, 2001;Johng et al, 2002;Lee et al, 2003;Ahn et al, 2005].…”
Section: Selection Resultsmentioning
confidence: 99%
“…Electrical skin measurements appear to vary significantly across body sites. Impedance graphs revealed that the mean impedance of PC6 at 1 kHz was approximately 500 kO while that of PC5 (a few cm away) was approximately 1300 kO [McCarroll and Rowley, 1979]. The median impedances at acupoint TW1 differed from the non-acupoint control (several inches away) by 5611 kO for the DC measurements (acupoint-12493 kO, control 6993 kO) and 483 kO for the AC measurements (acupoint-3496 kO, control 3979 kO) [Pearson et al, 2007].…”
Section: Acupuncture Points: Interpretationmentioning
confidence: 93%
“…Most devices used for electrical skin impedance have two electrodes, one of which is pressed manually against the skin by the examiner. [10][11][12] Variation in pressure and angle could signifi cantly infl uence the results. There is a need for further development of devices to measure electrical skin impedance.…”
Section: -7mentioning
confidence: 99%
“…Reports looking at whether APs have different electrical properties from non-APs are limited in number and conflicting [4,1216]. Nonetheless, a recent systematic review published by Ahn et al found evidence to support the contention that meridians and APs are electrically distinguishable from surrounding tissue [17].…”
Section: Introductionmentioning
confidence: 99%